Inovasi pendidikan abad 21: penerapan design thinking dan pembelajaran berbasis proyek dalam pendidikan Indonesia - Satria, Arif Bagas Adi; Muntaha, Arif Ali (Jurnal Pendidikan Dasar, 2021)
21st-century education is characterized by technological developments that are developing very rapidly, so daily learning must be in harmony with existing technology. Education in modern-day Indonesia requires innovation for more advanced learning. Therefore, Indonesia needs innovation to carry out learning that is following the nation's character, as well as a charactergemeinschaft (character builder) of students who will become the nation's next generation. The purpose of this study was to find out 21st-century educational innovations by applying design thinking to project-based learning in Indonesian education. The benefit of this research is that it can become a source of fresh scientific references among academics and become new reading material and literacy resources related to education. This study uses a descriptive qualitative approach with an emphasis on phenomenology. The method of data analysis in this study was carried out by descriptive analysis method, namely, the data obtained and then analyzed by descriptive analysis method. Indonesian education must include an innovation with the application of design thinking in project-based learning. Without an innovative “breakthrough”, Indonesian education cannot reach a point where the potential of students can be fully maximized.